Linguopoetic Characteristics of Imitative Words in Uzbek Literary Works - Khurramova Dilorom (International Journal Of Literature And Languages, 2025)
This article comprehensively studies the linguopoetic properties of imitative words in Uzbek literary works. In linguistics, imitative words are associated with the phenomenon of onomatopoeia, and they play an important role in creating aesthetic, emotional and semantic richness in the language by expressing sounds in nature, animal sounds, human movements or noises made by various objects. In particular, in literary works, it is observed that authors effectively use imitative words to create images, ensure a lively and natural expression of events, and increase the strength of aesthetic impact. The article analyzes the phonetic and morphological properties of imitative words, their function in poetic texts, and their role in enhancing imagery. The functional load of imitative words in the literary text, their importance as a factor determining the rhythm, melodiousness, and emotional tone of the text are shown through examples from the works of prominent representatives of Uzbek literature - Abdulla Qodiriy, Oybek, Cholpon, Erkin Vohidov, Amon Matjon, Muhammad Yusuf, and other poets and writers. The article also reveals the frequency of use of imitative words in poetic speech, their expressive power in creating an image, their role in conveying the national mentality and features of the folk language based on a linguopoetic approach. The relevance of the topic is substantiated by examples of the use of imitative words in folk oral creativity, legends, epics, fairy tales, and modern prose and poetic literature. The results of the article serve as an important theoretical and practical basis for determining the role and significance of imitative words in the poetic language, and for research in Uzbek linguistics and literary studies. This study advances scientific views based on the linguopoetic source necessary for a broader study of language culture, artistic aesthetic influence, poetic imagery methods, and the expressive potential of the vernacular.